Predictors of Millenials’ E-wallet Payment Behaviour in Post-Covid-19 in Malaysia - Hanudin Amin; Imran Mehboob Shaikh; Hamid Rizal; Esmadi Abu Abu Seman (Al Qasimia University, 2023)
This study uncovered contributing factors that could determine millennials’ e-wallet payment behaviour in post-coronavirus disease 2019 (COVID-19) in Malaysia. In this study, 256 millennial respondents from Labuan and Kota Kinabalu, Malaysia were approached using an online questionnaire via Google Forms for effective data collection. This study used the ‘attitude, social influence and self-efficacy’ (ASE) model as a baseline theory to explain millennials’ e-wallet payment behaviour in post-Covid-19. The results revealed that attitude, social influence and self-efficacy were significant predictors of e-wallet behaviour. Besides, attitude also served as a significant mediating variable. The results obtained should be considered with caution. At least two limiting factors are acknowledged in terms of the limited geographical locations as well as confined variables used to explain the behaviour. Besides these constraints, future research might examine other theories to contrast the findings for improved contributions in e-wallet payment in Malaysia. The results obtained would be very pertinent for the development of an e-wallet policy in post-Covid-19 and new guidelines to boost adoption for payment purposes in Malaysia. This study presents a new perspective on the potential impacts of millennials' e-wallet behaviour in post-COVID-19 in Malaysia using the ASE model.